2007
DOI: 10.2903/j.efsa.2007.434
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of the Scientific Panel on contaminants in the food chain [CONTAM] related to cyanogenic compounds as undesirable substances in animal feed

Abstract: SUMMARYHydrogen cyanide (HCN) is formed following the enzymatic hydrolysis of cyanogenic glycosides, which are produced as secondary metabolites by various plant species. In the intact plant these cyanogenic compounds are stored separated from hydrolytic enzymes. Crushing of plant materials either by technical processes or by chewing by animals obliterates this separation and initiates the enzymatic hydrolysis of cyanogenic compounds, resulting ultimately in the formation of HCN. Hydrolysis to release HCN can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 141 publications
(144 reference statements)
0
5
0
Order By: Relevance
“…One gram of prunasin can release 91.5 mg of HCN. As a consequence, HCN from rowan organs—when forming at levels exceeding 2–3 mg/(kg of human body weight)—can cause respiratory arrest and even death [ 44 ]. Therefore, cyanogenic glycosides that are present in rowan bark may perform a protective function for the plant, by preventing damage by ruminants [ 45 ] and insects [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…One gram of prunasin can release 91.5 mg of HCN. As a consequence, HCN from rowan organs—when forming at levels exceeding 2–3 mg/(kg of human body weight)—can cause respiratory arrest and even death [ 44 ]. Therefore, cyanogenic glycosides that are present in rowan bark may perform a protective function for the plant, by preventing damage by ruminants [ 45 ] and insects [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…When it is ingested small amounts of cyanogenic compounds, the most common route for detoxification is the conversion of hydrocyanic acid to thiocyanates in the liver and kidneys, which are subsequently excreted in the urine (Chaouali et al, 2013;Abraham, et al, 2016); importantly, the cyanide concentration is higher in erythrocytes than in plasma. Studies have shown that the cyanide level in different human tissues in a fatal case of HCN poisoning is 0.03 gastric content, 0.50 blood, 0.03 liver, 0.11 kidney, 0.07 brain, and 0.20 urine (mg/100 g) (EPA, 1990); toxic levels of cyanogenic glycosides are estimated based on the amount of free cyanide generated after hydrolysis (EFSA, 2007). However, a level of cyanide up to (10 mg L -1 ) has been reported as safe for cassava flour (FAO and WHO, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…European Food Safety Authority (EFSA) recommended following limits of HCN content in animal feed (mg HCN equivalents/ body weight per day): pigs -2.9 mg/kg per day, poultry -2.8 mg/kg per day, ruminants (on the basis of goat studies) -0.4 mg/kg per day. There is no literature data on tolerated levels of HCN in fish feed (EFSA, 2006;Ivanov et al, 2012).…”
Section: Introductionmentioning
confidence: 99%